Dyspnea in Patients Receiving Radical Radiotherapy for Non-Small Cell Lung Cancer: A Prospective Study - Sardaro, Angela; McDonald, Fiona; Bardoscia, Lilia; Lavrenkov, Konstantin; Singh, Shalini; Ashley, Sue; Traish, Daphne; Ferrari, Cristina; Meattini, Icro; Asabella, Artor Niccoli; Brada, Michael (Frontiers in Oncology, 2020)
Background and Purpose: Dyspnoea is an important symptomatic endpoint for assessment of radiation-induced lung injury (RILI) following radical radiotherapy in locally advanced disease, which remains the mainstay of treatment at the time of significant advances in therapy including combination treatments with immunotherapy and chemotherapy and the use of local ablative radiotherapy techniques. We investigated the relationship between dose-volume parameters and subjective changes in dyspnoea as a measure of RILI and the relationship to spirometry. Material and Methods: Eighty patients receiving radical radiotherapy for non-small cell lung cancer were prospectively assessed for dyspnoea using two patient-completed tools: EORTC QLQ-LC13 dyspnoea quality of life assessment and dyspnoea visual analogue scale (VAS). Global quality of life, spirometry and radiation pneumonitis grade were also assessed. Comparisons were made with lung dose-volume parameters. Results: The median survival of the cohort was 26 months. In the evaluable group of 59 patients there were positive correlations between lung dose-volume parameters and a change in dyspnoea quality of life scale at 3 months (V30 p=0.017; V40 p=0.026; V50 p=0.049; mean lung dose p=0.05), and a change in dyspnoea VAS at 6 months (V30 p=0.05; V40 p=0.026; V50 p=0.028) after radiotherapy. Lung dose-volume parameters predicted a 10% increase in dyspnoea quality of life score at 3 months (V40; p=0.041, V50; p=0.037) and dyspnoea VAS score at 6 months (V40; p=0.027) post-treatment. Conclusions: Worsening of dyspnoea is an important symptom of RILI. We demonstrate a relationship between lung dose-volume parameters and a 10% worsening of subjective dyspnoea scores. Our findings support the use of subjective dyspnoea tools in future studies on radiation-induced lung toxicity, particularly at doses below conventional lung radiation tolerance limits.